POLA INTEGRASI BUDAYA DALAM PENDEKATAN CULTURALLY RESPONSIVE TEACHING: KAJIAN LITERATUR (2010–2025) - Ema Raydani; Yeri Sutopo; Bambang Subali; Ellianawati (Universitas Negeri Medan, 2026)
Abstract: This study aim to analyze scientific publication trends and patterns of cultural integration in the implementation of Culturally Responsive Teaching (CRT) throuhout the 2010-2025 period. The research employed a bibliometric approach using Publish or Perish and VOSviewer, with a total of 62 selected articles identified through PRISMA criteria based on data retrieved from Google Scholar Scopus. The findings indicate a significant increase in CRT relate publications beginning in 2010, with the highest surge occurring in 2025, predominantly within elementary school settings and the IPAS sebject area. Cultural integration is implemented through the utilization of local culture based instructional media, contextual learning materials, and cross cultural collaboration in classroom practices. Future studies are recommended to broaden research in secondary and higher education levels in order to strengthen the implementation of Culturally Responsive Teaching (CRT). Keyword: Analysis Bibliometrics, Culturally Responsive Teaching, Cultural Integration, Multicultural Education Abstrak: Penelitian ini bertujuan untuk menganalisis tren publikasi ilmiah dan pola integrasi budaya dalam penerapan CRT selama priode 2010-2025. Metode penelitian menggunakan analisis bibliometrik dengan bantuan Publish or Perish dan Vosviewer dengan 62 artikel terpilih berdasarkan kriteria PRISMA berdasarkan data dari Google Scholar dan Scopus. Hasil menunjukkan peningkatan signifikan publikasi sejak tahun 2010 dengan puncak pada tahun 2025 didominasi jenjang sekolah dasar dan mata pelajaran IPAS. Integrasi budaya dilakukan melalui media berbasis budaya lokal, materi konstekstual dan kolaborasi lintas budaya. Penelitian selanjutnya direkomendasikan memperluas kajian pada pendidikan menengah dan tinggi untuk memperkuat implementasi Culturally ResponsiveI Teaching (CRT). Keyword: Analisis Bibliometrik, Integrasi Budaya, Kompetensi Budaya, Guru Pembelajaran Responsif Budaya, Pendidikan Multikultural